The Change from Past to Future for Adsorbent Materials in Treatment of Dyeing Wastewaters - Kyzas, George Z. (Materials (Basel), 2013)
Adsorption is one of the most promising decolorization techniques in dyeing wastewater treatment. Adsorption techniques for wastewater treatment have become more popular in recent years owing to their efficiency in the removal of pollutants too stable for biological methods. Dye adsorption is a result of two mechanisms (adsorption and ion exchange) and is influenced by many factors as dye/adsorbent interaction, adsorbent’s surface area, particle size, temperature, pH, and contact time. The main advantage of adsorption recently became the use of low-cost materials, which reduces the procedure cost. The present review firstly introduced the technology process, research history and research hotspot of adsorption. Then, the application of adsorption in treatment of dyeing wastewaters in the past decades was summarized, revealing the impressive changes in modes, trends, and conditions. From this review article, the different philosophy of synthesis of adsorbent materials became evident.